Pengaruh Penerapan Pendidikan Agama Kristen Terhadap Penanaman Nilai Kesabaran Anak Usia 4-6 Tahun Di TK Elfrida Harder HKBP Siborongborong (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The aim of this research is to determine the effect of implementing Christian Religious Education on the value of cultivating patience in children aged 4-6 years at Elfrida Harder Kindergarten HKBP Siborongborong. The research method used is a quantitative descriptive research method. The population is all group B students (aged 4-6 years) at Kindergarten Elfrida Harder HKBP Siborongborong totaling 35 people. Data collected using a positive closed questionnaire consisted of 10 items for variable Test analysis requirements: a) test the relationship that obtains a positive value rxy = 0,568 > rtabel(α=0,05,n=35) = 0,334. b) A significant relationship test is obtained thitung= 3,967 > ttabel(α =0,05,dk=n-2=33)= 2,042. 2) Influence test: a) Test the regression equation, obtain the regression equation . b) Regression coefficient of determination test (r2) = 32.3%. 3) Test the hypothesis using the F test to obtain Fhitung > Ftabel=( α =0,05,dk pembilang k=12,dk penyebut=n-2=35-2=33) namely 15.73 > 2.09. Thus Ha, that is, there is an influence of the application of Christian Religious Education on instilling the value of patience in children aged 4-6 years at TK Elfrida Harder HKBP Siborongborong is accepted and H0 is rejected.